Role theory in symbolic interactionism: Czech Republic, Germany and the EU - Benes̆, Vít; Harnisch, Sebastian (Cooperation and conflict, 2015)
The literature on norm socialization and Europeanization has largely focused on successful norm diffusion, but thus far it has hardly addressed the norm backlas...
First Published March 18, 2014
Gesehen am 20.05.2020
Keywords: Europäische Union; Deutschland; Tschechien